Assessing the Causes of Time Overrun in Building and Road Construction Projects: The Case of Addis Ababa City, Ethiopia - Adamu Beyene Negesa (Journal of Engineering)
In recent years, the majority of the construction projects executed in Addis Ababa city experienced a varying magnitude of time overrun in which the projects become late in their completion. Due to different problems encountered during the inception, design, and implementation phases, the projects are exposed to unexpected time overruns that in turn affect the overall performance of the projects. It is hence very essential to identify the actual causes of delay in order to minimize or avoid the corresponding adverse impacts. Therefore, this study primarily aimed at investigating and scrutinizing the potential factors causing project time overrun in the city so that the influential factors can be identified and the applicable remedial measures can possibly be forwarded. For the purpose of data collection, the study applied a semistructured questionnaire survey. The questionnaire was distributed to 121 respondents comprising practitioners and professionals actively working in the construction industry. Fifty-four delay-causing factors were identified and grouped under ten categories according to the similarity of their origin. In order to identify the most significant factors, severity analysis based on the principle of relative importance index was carried out. Accordingly, the top most significant and least significant factors were identified. The top four most influential factors identified were reluctance of consultants, inaccurate estimation of contract duration, delay in approvals and late decision making, and slow mobilization of labor whereas inadequacy of allocated funds, low motivation, and absence of incentives to contractors were the three least significant causes identified. So as to curb the adverse impact of the factors, the application of a detailed work breakdown structure, proper responsibility assignment, earned value principle, and project software were proposed as remedial measures to be implemented. The finding of the study will alarm the key players and practitioners engaging in the city’s construction industry to focus on managing the severe factors.